(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the linguoculturological features of English idioms and their role in reflecting national culture, history, and mentality. Idioms are considered important linguistic units that express the worldview and cultural values of English-speaking people. The study analyzes the figurative meanings, historical origins, and cultural background of English idiomatic expressions. Special attention is given to the difficulties of translating idioms into other languages because of their culture-specific meanings. The article also highlights the importance of idioms in intercultural communication and language learning. The research shows that idioms serve not only as language elements but also as carriers of cultural identity and national traditions.